An investigation into the Effects of Intravenous Vitamin C on Pulmonary CT Findings and Clinical Outcomes of Patients with COVID 19 Pneumonia A Randomized Clinical Trial - Tehrani, Shabnam; Yadegarynia, Davood; Abrishami, Alireza; Moradi, Hamideh; Gharaei, Babak; Rauofi , Masoomeh; Maghsoudi Nejad, Fatemeh; Sali, Shahnaz; Khabiri, Neda; Abolghasemi, Sara (Urology Journal, 2022)
Purpose:In late December 2019, a series of unexplained cases of pneumonia were reported in Wuhan, China. On January 12, 2020, the World Health Organization temporarily named the virus responsible for the emerging cases of pneumonia as the 2019 coronavirus. Acute respiratory distress syndrome (ARDS) due to Covid-19 has rapidly spread around the world, and while no specific treatment or vaccine has been reported, mortality rates remain high. One of the suggested treatments for cellular damage in the pathogenesis of ARDS caused by the coronavirus is the administration of high doses of intravenous vitamin C. Considering the paucity of literature on the therapeutic effects of high doses of intravenous vitamin C in patients with ARDS resulting from the coronavirus, this study was conducted to assess this therapeutic supplement in these patients. Materials and Methods: This study was performed as a single-center clinical trial in patients with a documented diagnosis of COVID-19 pneumonia. 54 eligible patients with moderate to severe COVID-19 symptoms, based on specific inclusion and exclusion criteria, were included in the investigation and randomly divided into two groups. The control group consisted of 26 patients who received standard treatment, whereas the treatment group was comprised of 18 patients administered intravenous vitamin C at a dose of 2 g every 6 hours for 5 days in addition to standard treatment. Demographic characteristics, underlying diseases, length of hospital stay, and mortality rates were reviewed and collected. Oxygen saturation, respiratory rates, serum C Reactive Protein (CRP) levels, lymphopenia and lung parenchymal involvement on CT were investigated at the time of admission and on the sixth day after hospitalization. Finally, all variables were analyzed with IBM SPSS Statistics 23 software and a significant statistical difference was defined for all variables, P <0.05. Results: Of these variables, the amount of oxygen saturation in the vitamin C group increased significantly from 86±5% on the first day of hospitalization to 90±3% on the sixth day of hospitalization (P value=0.02). Also, the respiratory rate in the vitamin C group decreased significantly from 27±3 on the first day of hospitalization to 24±3 on the sixth day of hospitalization (P value=0.03). Lung CT scans of patients in the two groups reported by two radiologists were also compared. Based on the report of the radiologists, the rate of lung involvement in the vitamin C group was significantly lower than in the control group at the end of treatment (P value=0.02). Conclusion: Due to the effectiveness of high doses of intravenous vitamin C on reducing lung involvement and improving clinical symptoms, further studies with a larger sample size are recommended to demonstrate the effects of this drug supplement.